Pakistan : Seventh, and Eighth Reviews of the Extended Arrangement under the Extended Fund Facility, Requests for Waivers of Nonobservance of Performance Criteria, and for Extension, Augmentation, and Rephasing of Access-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Pakistan. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2022)
Economic activity remained robust in FY22, fueled by loose fiscal policy and a delayed monetary response to inflationary pressures. These combined with the international food and fuel price shocks led to a marked deterioration of the external position with an unsustainable current account deficit, a significant decline in reserves, and a marked depreciation of the rupee. At the same time, inflation has increased considerably, putting pressure particularly on the more vulnerable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Pakistan